Method for preparing composite flocculant by utilizing lithium slag

By preparing a composite flocculant, the problem of insufficient resource utilization of lithium slag was solved, and the recovery and utilization of valuable elements in lithium slag and the improvement of flocculation effect were realized.

CN119680997APending Publication Date: 2025-03-25GANFENG LITHIUM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411943607.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The resource utilization rate of lithium slag is low, and its stockpiling and leaching processes may cause environmental damage. Existing technologies are unable to effectively recover valuable elements from lithium slag.

Method used

A composite flocculant was prepared by reacting lithium slag with a dissociation agent, filtering the mixture, adding alkaline solution for alkali polymerization, followed by evaporation, crystallization, and drying.

Benefits of technology

The resource utilization of lithium slag has been improved, and the prepared composite flocculant has a good flocculation effect, completing the flocculation process in a short time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680997A_ABST
    Figure CN119680997A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium slag resource utilization, and provides a method for preparing a composite flocculant by utilizing lithium slag. The method comprises the following steps: reacting the lithium slag with a dissociation agent, and filtering to obtain an aluminum-iron-calcium-magnesium mixed salt solution; adding alkali liquor into the aluminum-iron-calcium-magnesium mixed salt solution, and carrying out alkalization polymerization reaction to obtain a polymerized salt solution; the polymeric salt solution is sequentially subjected to evaporative crystallization and drying, and the composite flocculant is obtained. According to the method, the lithium slag is used as a raw material, valuable elements in the lithium slag are recycled, the composite flocculant is prepared, and the resource recycling degree of the lithium slag is improved. The composite flocculant combines the advantages of aluminum salt, calcium salt, ferric salt and magnesium salt, and is short in flocculation time and good in flocculation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium slag resource utilization, and in particular to a method for preparing a composite flocculant by utilizing lithium slag. Background Art

[0002] With the increasing demand for lithium salts, the amount of lithium smelting slag (i.e. lithium slag) produced by lithium extraction is also growing continuously. For every ton of lithium salt produced, 8 to 10 tons of lithium slag will be produced. It is estimated that by 2025, the annual output of lithium slag in Yichun City will reach 15 million tons, entering the level of bulk industrial solid waste. Lithium slag contains metal elements such as Al, Fe, and Ca. During the stacking, leaching and percolation process, the metal elements may enter the groundwater, soil and atmospheric environment, causing harm to the ecosystem and the health of the human living environment. Therefore, how to safely dispose of and recycle lithium slag is an issue that must be considered in the development of lithium salts. The metal elements in lithium slag can be extracted by leaching, and quartz and feldspar can be used to prepare building materials such as cement, concrete, and ceramics. However, the current level of resource utilization of lithium slag is low.

[0003] Inorganic polymer flocculants are a new type of water treatment agent developed on the basis of traditional flocculants (such as aluminum salts and iron salts). They have better flocculation effects than traditional flocculants when treating wastewater containing fine particles, and are cheaper than organic polymer flocculants. Lithium slag mainly contains SiO2, Li2O, Al2O3, Fe2O3, CaO, MgO, etc., and the total content is usually above 95%. It is rich in the main ingredients for preparing aluminum-based inorganic polymer flocculants and is a natural raw material for preparing inorganic polymer flocculants.

[0004] Based on this, a method for preparing a composite flocculant using lithium slag as a raw material is provided, and the aluminum, iron, calcium and magnesium in the lithium slag are recycled, which has broad application prospects for the resource utilization of lithium slag and wastewater treatment. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a composite flocculant using lithium slag in view of the deficiencies in the prior art.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a composite flocculant using lithium slag, comprising the following steps:

[0008] 1) reacting the lithium slag and the dissociating agent and filtering them to obtain an aluminum, iron, calcium and magnesium mixed salt solution;

[0009] 2) adding alkali solution to the aluminum, iron, calcium and magnesium mixed salt solution to carry out alkalization polymerization reaction to obtain a polymerized salt solution;

[0010] 3) The polymerized salt solution is evaporated, crystallized and dried in sequence to obtain a composite flocculant.

[0011] Preferably, the lithium slag in step 1) comprises one or more of spodumene smelting slag, lepidolite smelting slag, petalite smelting slag and pyroxenite smelting slag, and the particle size of the lithium slag is 200-400 mesh;

[0012] The dissociating agent comprises one or more of oxalic acid, sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, acetic acid, sodium sulfate solution, ammonium chloride solution, sodium bisulfate solution and sodium bisulfite solution.

[0013] Preferably, in step 1), the mass ratio of the lithium slag to the dissociating agent is 1:5-10, and the mass concentration of the dissociating agent is 5-20%;

[0014] The reaction temperature is 40-95° C., and the reaction time is 1-4 hours.

[0015] Preferably, the alkali solution in step 2) comprises one or more of sodium hydroxide solution, calcium hydroxide solution and ammonia water, and the mass concentration of the alkali solution is 30-40%.

[0016] Preferably, the temperature of the alkalization polymerization reaction in step 2) is 25 to 85° C., the time of the alkalization polymerization reaction is 1 to 2 hours, and the pH value of the alkalization polymerization reaction is 1.5 to 4.5;

[0017] The step of adding alkali solution to the mixed salt solution of aluminum, iron, calcium and magnesium is stopped when the pH value reaches the pH value of the alkalization polymerization reaction.

[0018] Preferably, the temperature of the evaporation crystallization in step 3) is 95-110° C., and the time of the evaporation crystallization is 1-2 h.

[0019] Preferably, the drying temperature in step 3) is 45-80° C. and the drying time is 4-6 hours.

[0020] Beneficial effects of the present invention:

[0021] The present invention uses lithium slag as raw material, recycles valuable elements in the lithium slag, prepares a composite flocculant, and improves the resource recycling degree of lithium slag. The composite flocculant of the present invention combines the advantages of aluminum salt, calcium salt, iron salt, and magnesium salt, has a short flocculation time and a good flocculation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the X-ray diffraction pattern of the composite flocculant prepared in Example 1. DETAILED DESCRIPTION

[0023] The present invention provides a method for preparing a composite flocculant using lithium slag, comprising the following steps:

[0024] 1) reacting the lithium slag and the dissociating agent and filtering them to obtain an aluminum, iron, calcium and magnesium mixed salt solution;

[0025] 2) adding alkali solution to the aluminum, iron, calcium and magnesium mixed salt solution to carry out alkalization polymerization reaction to obtain a polymerized salt solution;

[0026] 3) The polymerized salt solution is evaporated, crystallized and dried in sequence to obtain a composite flocculant.

[0027] In the present invention, the lithium slag in step 1) preferably comprises one or more of spodumene smelting slag, lepidolite smelting slag, petalite smelting slag and pyroxenite smelting slag, and the particle size of the lithium slag is preferably 200-400 mesh, more preferably 250-350 mesh, and more preferably 300 mesh;

[0028] The dissociating agent preferably comprises one or more of oxalic acid, sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, acetic acid, sodium sulfate solution, ammonium chloride solution, sodium bisulfate solution and sodium bisulfite solution.

[0029] In the present invention, in step 1), the dissociating agent is preferably added to the lithium slag, and stirring is performed during the adding process. The stirring speed is preferably 400-600 rpm, and more preferably 500 rpm.

[0030] In the present invention, the mass ratio of the lithium slag to the dissociating agent in step 1) is preferably 1:5-10, more preferably 1:6-9, and more preferably 1:7-8; the mass concentration of the dissociating agent is preferably 5-20%, more preferably 10-15%, and more preferably 12%;

[0031] The reaction temperature is preferably 40 to 95° C., more preferably 60 to 85° C., and more preferably 65 to 75° C.; the reaction time is preferably 1 to 4 h, more preferably 1.5 to 3 h, and more preferably 2 to 2.5 h.

[0032] In the present invention, the alkali solution in step 2) preferably comprises one or more of sodium hydroxide solution, calcium hydroxide solution and ammonia water, and the mass concentration of the alkali solution is preferably 30-40%, more preferably 32-37%, and more preferably 35%.

[0033] In the present invention, the temperature of the alkalization polymerization reaction in step 2) is preferably 25 to 85° C., more preferably 40 to 60° C., and more preferably 45 to 55° C.; the time of the alkalization polymerization reaction is preferably 1 to 2 hours, more preferably 1.2 to 1.8 hours, and more preferably 1.5 hours; the pH value of the alkalization polymerization reaction is preferably 1.5 to 4.5, more preferably 2 to 4, and more preferably 2.5 to 3.5;

[0034] The addition of alkali solution is preferably stopped when the pH value of the aluminum, iron, calcium and magnesium mixed salt solution reaches the pH value of the alkalization polymerization reaction.

[0035] In the present invention, the temperature of the evaporation crystallization in step 3) is preferably 95-110° C., more preferably 100-105° C., and more preferably 102° C.; the time of evaporation crystallization is preferably 1-2 h, and more preferably 1.5 h.

[0036] In the present invention, the drying temperature in step 3) is preferably 45 to 80° C., more preferably 55 to 75° C., and more preferably 60 to 65° C.; the drying time is preferably 4 to 6 h, more preferably 4.5 to 5.5 h, and more preferably 5 h.

[0037] In the present invention, the general formula of the composite flocculant is [Al (13-x) Fe x CaMgNaSi y O 22 (OH)2] m Cl (24-Z)· nH2O, where 0≤x≤5, 0≤y≤8, 0≤z≤24, 0≤m≤12, 0≤n≤10.

[0038] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0039] Example 1

[0040] 100g of spodumene smelting slag with a particle size of 200 mesh is placed in a reactor, the reactor temperature is controlled at 65°C, 600g of hydrochloric acid (the mass concentration of hydrochloric acid is 15%) is added to the reactor, and the mixture is stirred at a speed of 400rpm during the addition process. After the addition is completed, the reaction is carried out for 2h, and the reaction product is filtered to obtain an aluminum iron calcium magnesium mixed salt solution. The aluminum iron calcium magnesium mixed salt solution is placed in a 45°C environment, and sodium hydroxide solution (the mass concentration of the sodium hydroxide solution is 32%) is added to the aluminum iron calcium magnesium mixed salt solution. When the pH value of the obtained mixed solution is 2.5, the addition of sodium hydroxide solution is stopped, and an alkalization polymerization reaction is started for 1h to obtain a polymerized salt solution. The polymerized salt solution is placed at 105°C for evaporation and concentration for 1h to precipitate crystals, and the crystals are placed at 60°C for drying for 5h to obtain a composite flocculant with a mass of 32g.

[0041] Example 2

[0042] 200g of lithium mica smelting slag with a particle size of 300 mesh is placed in a reactor, the reactor temperature is controlled at 70°C, 2000g of hydrochloric acid (the mass concentration of hydrochloric acid is 12%) is added to the reactor, and the mixture is stirred at a speed of 600rpm during the addition process. After the addition is completed, the reaction is carried out for 1.5h, and the reaction product is filtered to obtain an aluminum iron calcium magnesium mixed salt solution. The aluminum iron calcium magnesium mixed salt solution is placed in a 50°C environment, and a calcium hydroxide solution (the mass concentration of the calcium hydroxide solution is 32%) is added to the aluminum iron calcium magnesium mixed salt solution. When the pH value of the obtained mixed solution is 1.5, the addition of the calcium hydroxide solution is stopped, and an alkalization polymerization reaction is started for 1h to obtain a polymerized salt solution. The polymerized salt solution is placed at 102°C for evaporation and concentration for 2h, and crystals are precipitated. The crystals are placed at 60°C and dried for 5h to obtain a composite flocculant with a mass of 58g.

[0043] Example 3

[0044] 200g of spodumene smelting slag with a particle size of 400 mesh is placed in a reactor, the reactor temperature is controlled at 85°C, 1000g of hydrochloric acid (the mass concentration of hydrochloric acid is 15%) is added to the reactor, and the mixture is stirred at a speed of 500rpm during the addition process. After the addition is completed, the reaction is carried out for 1h, and the reaction product is filtered to obtain an aluminum iron calcium magnesium mixed salt solution. The aluminum iron calcium magnesium mixed salt solution is placed in a 40°C environment, and ammonia water (the mass concentration of ammonia water is 32%) is added to the aluminum iron calcium magnesium mixed salt solution. When the pH value of the obtained mixed solution is 2, the addition of ammonia water is stopped, and an alkalization polymerization reaction is started for 1h to obtain a polymerized salt solution. The polymerized salt solution is placed at 100°C for evaporation and concentration for 1.5h, crystals are precipitated, and the crystals are placed at 60°C for drying for 5h to obtain a composite flocculant with a mass of 62g.

[0045] Example 4

[0046] 200g of 300-mesh petalite smelting slag is placed in a reactor, the reactor temperature is controlled at 95°C, 1600g of oxalic acid (the mass concentration of oxalic acid is 5%) is added to the reactor, and the mixture is stirred at a speed of 500rpm during the addition process. After the addition is completed, the reaction is carried out for 1h, and the reaction product is filtered to obtain an aluminum iron calcium magnesium mixed salt solution. The aluminum iron calcium magnesium mixed salt solution is placed in a 60°C environment, and sodium hydroxide solution (the mass concentration of the sodium hydroxide solution is 35%) is added to the aluminum iron calcium magnesium mixed salt solution. When the pH value of the obtained mixed solution is 3.5, the addition of sodium hydroxide solution is stopped, and an alkalization polymerization reaction is started for 1.5h to obtain a polymerized salt solution. The polymerized salt solution is placed at 95°C for evaporation and concentration for 2h to precipitate crystals, and the crystals are placed at 45°C for drying for 6h to obtain a composite flocculant with a mass of 50g.

[0047] Example 5

[0048] 200g of 300-mesh phosphate lithium aluminum smelting slag is placed in a reactor, the reactor temperature is controlled at 40°C, 1400g of acetic acid (the mass concentration of acetic acid is 20%) is added to the reactor, and the mixture is stirred at a speed of 480rpm during the addition process. After the addition is completed, the reaction is carried out for 4h, and the reaction product is filtered to obtain an aluminum iron calcium magnesium mixed salt solution. The aluminum iron calcium magnesium mixed salt solution is placed in an environment of 85°C, and ammonia water (the mass concentration of ammonia water is 40%) is added to the aluminum iron calcium magnesium mixed salt solution. When the pH value of the obtained mixed solution is 4.5, the addition of ammonia water is stopped, and an alkalization polymerization reaction is started for 2h to obtain a polymerized salt solution. The polymerized salt solution is placed at 110°C for evaporation and concentration for 2h to precipitate crystals, and the crystals are placed at 80°C for drying for 4h to obtain a composite flocculant with a mass of 55g.

[0049] At a pH value of 6.5, 1 g of the composite flocculant of Examples 1 to 5 and 1 g of polyaluminium chloride flocculant were used to flocculate 500 mL of aqueous solution (containing 1 g of diatomaceous earth), and the flocculation time was recorded. The flocculation results are shown in Table 1.

[0050] Table 1 Flocculation results of different flocculants

[0051]

[0052]

[0053] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a composite flocculant using lithium slag, characterized in that: The following steps are included: 1) reacting the lithium slag and the dissociating agent and filtering them to obtain an aluminum, iron, calcium and magnesium mixed salt solution; 2) adding alkali solution to the aluminum, iron, calcium and magnesium mixed salt solution to carry out alkalization polymerization reaction to obtain a polymerized salt solution; 3) The polymerized salt solution is evaporated, crystallized and dried in sequence to obtain a composite flocculant.

2. The method according to claim 1, characterized in that Step 1) the lithium slag comprises one or more of spodumene smelting slag, lepidolite smelting slag, petalite smelting slag and pyroxenite smelting slag, and the particle size of the lithium slag is 200-400 mesh; The dissociating agent comprises one or more of oxalic acid, sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, acetic acid, sodium sulfate solution, ammonium chloride solution, sodium bisulfate solution and sodium bisulfite solution.

3. The method according to claim 1 or 2, characterized in that: Step 1) The mass ratio of the lithium slag to the dissociating agent is 1:5-10, and the mass concentration of the dissociating agent is 5-20%; The reaction temperature is 40-95° C., and the reaction time is 1-4 hours.

4. The method according to claim 3, characterized in that Step 2) The alkali solution comprises one or more of sodium hydroxide solution, calcium hydroxide solution and ammonia water, and the mass concentration of the alkali solution is 30-40%.

5. The method according to claim 4, characterized in that Step 2) the temperature of the alkalization polymerization reaction is 25 to 85° C., the time of the alkalization polymerization reaction is 1 to 2 hours, and the pH value of the alkalization polymerization reaction is 1.5 to 4.5; The step of adding alkali solution to the mixed salt solution of aluminum, iron, calcium and magnesium is stopped when the pH value reaches the pH value of the alkalization polymerization reaction.

6. The method according to claim 4 or 5, characterized in that: Step 3) The temperature of the evaporation crystallization is 95-110° C., and the time of the evaporation crystallization is 1-2 hours.

7. The method according to claim 6, characterized in that Step 3) The drying temperature is 45 to 80° C. and the drying time is 4 to 6 hours.

Citation Information

Patent Citations

  • Method of using lithium-extracted waste residue to prepare polymerized aluminum calcium chloride water purifying agent

    CN105836864A

  • Method for preparing efficient composite flocculant by taking red mud as raw material

    CN112093870A

  • Method for preparing calcium aluminum ferric polysilicate from coal gasification slag

    CN115465869A

  • Method for preparing polysilicate aluminum ferric-PAM composite flocculant by using red mud as raw material

    CN118791098A

  • Lithium slag-based composite cementing material and preparation method thereof

    CN119080410A